Pergeseran struktur jangkar karir dominan: Bukti pada karyawan media cetak - Meiliani Meiliani; Raga Arie Sagita Nugroho; Jahja Hamdani Widjaja (Universitas Kristen Maranatha, 2023)
Career anchor is an intrinsic motivation that drives an individual to pursue what they want to achieve in their career goals. The aim of this study is to reveal individuals internal career orientations using the concept of career anchors. This research is a case study to uncover the dominant career anchor, assess group-based career anchors, and analyze the relationship between career anchors to understand the shifting structure and content of the career anchor concept. Using the purposive sampling method, 49 employees working in a print media company in Bengkulu Province were selected as informants and asked to fill out an online questionnaire. Valid data were analyzed using an octagonal diagram. The results revealed that economic security emerged as the dominant career anchor followed by multiple career anchors. Autonomy, challenge, and service career anchors were not appealing to them. The needs-based career anchors consisting of economic security, geographic stability, and lifestyle was the most preferred group-based anchor categories among the respondents and proved that various career anchors become work goals. However, no employee chose the values-needs career anchor. It was found that all career anchor relationships were complementary. These results question the concept that an individual only has one dominant career anchor and contribute to the concept of multiple career anchors. The print media employees themselves prefer to perform all kinds of work that can meet their basic needs rather than being creative. It is recommended that companies can create flexibility in employee work that accommodate these needs so that they can be innovative.